TEACHER’S STRATEGIES IN TEACHING ENGLISH SPEAKING AT MAN 2 PALEMBANG - SAPUTRA, EKO; ERLINA, DIAN; DITA, SYANIN (Linguists : Journal of Linguistics and Language Teaching, 2023)
The purpose of this study was to determine how a teacher at MAN 2 Palembang taught English to a bilingual class of tenth-graders. Case study qualitative research was used as the research design for this study. The researchers used interviews to gather in-depth information about the English teacher's instructional strategies. The participant was one of the English teachers at MAN 2 Palembang and was selected using a sampling technique known as purposive sampling. The researchers used thematic analysis to analyze the data in order to obtain information about the difficulties in teaching speaking skills at MAN 2 Palembang. The findings revealed that there were three strategies used by the teacher in teaching English: (1) the teacher used a combination of role plays and storytelling; (2) the teacher used a combination of brainstorming, group discussion, and oral presentation; and (3) the teacher used ice-breaking and conversation for teaching English. The teacher utilized the technique because it is straightforward and based on a manual. The teacher also utilized additional methods. It could be concluded that the majority of students enjoy the teacher's strategies.